Federalism and the Madheshi People: A Struggle for Equality and Inclusion (Research Journal of Padmakanya Multiple Campus, 2024)
This article presents the view of the federal structure of Nepal and the issues related to Madhesh and Madheshi people along with their struggle for equality and inclusion. Federalism was felt necessary in Nepal due to the dissatisfaction of diverse group of peoples' demand of self- governance, inclusion, identity, rights etc. and to strengthen the democracy and sovereignty of the nation if the social diversity is addressed. The study is primarily based on conceptual and narrative literature review, used the liberal philosophy of political science, a contemporary institutional approach, and a descriptive and analytical methodology that mostly uses secondary sources of data. As federalism is introduced in the country in recent past, it is still in transition period to fulfil the will and aspiration of the people because it is not addressing full autonomy and self-governance to the provinces. Though Madheshi peoples' fight for inclusion and equality, through which the Madheshi Movement forced the government to amend the 2015 constitution in order to improve sustainability, national integrity, and inclusive democracy and equal status, Madheshi people are not satisfied in concern with proportional representation and power sharing. Yet, we cannot forget the significance of federalism which is the outcome of a struggle for equality and inclusion in Nepal concerning with Madhesh and Madheshi people and it paved the way of balanced development and self-decision making power to the provincial and local government.